Schooling and citizenship: evidence from compulsory schooling reforms - Thomas Siedler (Institute for the Study of Labor (IZA), 2007)
This paper examines whether schooling has a positive impact on individual's political interest, voting turnout, democratic values, political involvement and political group membership, using the German General Social Survey (ALLBUS). Between 1949 and 1969 the number of compulsory years of schooling was increased from eight to nine years in the Federal Republic of Germany, gradually over time and across federal states. These law changes allow one to investigate the causal impact of years of schooling on citizenship. Years of schooling are found to be positively correlated with a broad range of political outcome measures. However, when exogenous increase in schooling through law changes is used, there is no evidence of a causal effect running from schooling to citizenship in Germany.
urn:nbn:de:101:1-20080425224
Keywords: 330; Schulpolitik; Bildungsverhalten; Öffentliches Interesse; Politische Willensbildung; Partizipation; Deutschland